Städtebaulicher Ideen- und Realisierungswettbewerb Süßen. - (:unkn) unknown (My University, 1980)
1. Preis: Wilhelm Mathes, Stuttgart; 2. Preis: Fritz Elsaesser, Albrecht Gluecker, Albrecht Pfaff, Wolfgang Weller, Stuttgart; 3. Preis: Hans Scheele, Stuttgart; 4. Preis: Hans Ulrich Linder, Hans-Rolf Sommer, Hermann Kugler, Stuttgart; 5. Preis: Gerhard Keller, Süßen. -y-
Keywords: Stadtplanung/Städtebau; Bebauungsplanung; Sanierung; Stadtteilplanung; Wettbewerb; Wohnen; Ideenwettbewerb; Realisierungswettbewerb; Bauwettbewerb; Altenheim; Gemeindezentrum; Wohngebäude; Handelsgebäude; Bürogebäude